NOVUM AND UNREVEALED DATA IN TAX DISPUTES IN INDONESIA: A LEGAL CERTAINTY PERSPECTIVE - Risanto Risanto; Arief Hakim P. Lubis (Journal of Tax Law and Policy, 2022)
The previously novum and undisclosed data are still (potentially) a problem in tax administration in Indonesia, as the facts show that there are several court decisions regarding the issuance of additional tax underpayment assessment letters (SKPKBT). It is necessary to conduct a study expected to produce legal concepts from the novum and data that were not previously disclosed to provide legal certainty to taxpayers and the state. Based on the normative juridical method, two conclusions were drawn. First, the novum arrangement and/or data that are seriously disclosed in the Elucidation of Article 15 paragraph (1) of the KUP Law, PMK Number 145/PMK.03/2012 in conjunction with PMK Number 18/PMK.03/2021, and SE-33/PJ. 31/1990 is still unclear, biased, and contains multiple meanings or provides an opportunity to be interpreted differently. Second, there is a renewal of understanding and/or understanding of novum and/or data that were not previously disclosed, which should reach the principles of propriety to act or act and propriety not to work or not to act against taxpayers and tax authorities. It is recommended that the sentence structure, wording, and use of the term novum and/or previously undisclosed data, which will later be standardized in tax laws and regulations, refer to data, documents, evidence, and parts of data, documents, and evidence. - evidence that is not used as the basis for issuing a tax assessment letter following the provisions of the legislation in the field of taxation.